Communism in crisis in Britain and abroad, 1931-1979. - Communist Party of Great Britain; Communist Party of Great Britain. Archive Trust (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2021)
John Gollan (1911-1977) was a political leader and communist activist in Britain during the 20th century. Gollan joined the Communist Party of Great Britain (CPGB) in 1926 following his involvement in the General Strike of the same year. A close apprentice and confidante of Harry Pollitt, he was seen as the most appropriate and able person to take over his crucial role of General Secretary in 1956.
Date range: 1931-1979.
Keywords: Gollan, John; Communist Party of Great Britain; Communist leadership -- Great Britain